(untitled) (Bangladesh Journal of Neuroscience, 2026)
Background: Troponin I is recognized as sensitive and specific marker of myocardial injury. But elevation of troponin I can occur after acute ischemic stroke in absence of primary cardiac causes. Objective: The study was planned to evaluate the association of troponin I level with severity of neurological disability in acute Ischemic Stroke patient and their in-hospital outcome. Methods: This cross-sectional study was conducted in the department of Neurology and department of Medicine, Mymensingh Medical College & Hospital from July, 2018 to June, 2019. Total 115 purposively selected patients with acute ischemic stroke were evaluated. Diagnosis was confirmed by CT scan of brain. Serum troponin I was measured for each patients within 24 hours of admission. National Institute of Health Stroke Scale (NIHSS) was used to assess severity of stroke within 48hours of admission. Modified Rankin Scale (mRS) was used to evaluate outcome during discharge. Results: Mean age of acute ischemic stroke patients was 59.5±13.8 years with male predominance (62.6%). Mean age of elevated troponin I group was significantly higher than that of non-elevated group (70.9 vs. 57.2 years). Almost half of the respondents (44.3%) scored 1-4 (minor stroke), 38.3% had scored 5-15 (moderate stroke), 14.8% had scored 16-20 (Moderate to severe stroke) and 2.6% had scored greater than 20 (severe stroke). Moderate to severe stroke was significantly higher in elevated TnI group compare to non-elevated TnI group. Elevated troponin I (TnI) was found in 19(16.5%) cases and 96(83.5%) patients had TnI level<0.3 ng/ml (Nonelevated). The mean serum cardiac troponin I values in all patients was 0.294±0.547ng/ mL. Comparing to patients with non-elevated TnI group, patients with elevated TnI had higher mean NIHSS scores on admission (16.4 vs. 5.35). The mean mRs score was also higher for the elevated TnI group compare to non-elevated TnI group during discharge (5.21 vs. 2.57). The mean length of hospital stay (days) was higher in elevated TnI group compare to non-elevated TnI group (7.42 vs. 4.03). Multivariate analysis revealed that age e” 60 years (Odd ratio [OR] 1.12, CI [1.01–2.94]), NIHSS score e”12 on admission (OR 4.29, CI [1.04–11.29]), and elevated TnI (OR 2.58, CI [2.07–6.02]) were associated with in-hospital outcome. Conclusion: Elevated serum TnI levels were associated with increased severity of acute ischemic stroke and in-hospital outcome.